2011
DOI: 10.1002/mrc.2772
|View full text |Cite
|
Sign up to set email alerts
|

Structure elucidation of the new citharoxazole from the Mediterranean deep‐sea sponge Latrunculia (Biannulata) citharistae

Abstract: Citharoxazole (1), a new batzelline derivative featuring a benzoxazole moiety, was isolated from the Mediterranean deep-sea sponge Latrunculia (Biannulata) citharistae Vacelet, 1969, together with the known batzelline C (2). This is the first chemical study of a Mediterranean Latrunculia species and the benzoxazole moiety is unprecedented for this family of marine natural products. The structure was mainly elucidated by the interpretation of NMR spectra and especially HMBC correlations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 16 publications
3
14
0
Order By: Relevance
“…The benzoxazole moiety in makaluvamine W ( 433 ) is also found in citharoxazole ( 435 ), isolated from the sponge Latrunculia (Biannulata) citharistae in 2011 ( Figure 60 ). The latter compound represented the first oxazole derivative in this family at that time [ 329 ].…”
Section: Miscellaneousmentioning
confidence: 99%
“…The benzoxazole moiety in makaluvamine W ( 433 ) is also found in citharoxazole ( 435 ), isolated from the sponge Latrunculia (Biannulata) citharistae in 2011 ( Figure 60 ). The latter compound represented the first oxazole derivative in this family at that time [ 329 ].…”
Section: Miscellaneousmentioning
confidence: 99%
“…The only compound in the study that fulfilled all of the criteria to be considered lead-like was from an organism of the Animalia Kingdom, citharoxazole, which was isolated from the deep-sea Mediterranean sponge, Latrunculia (Biannulata) citharistae from a depth of 103 m off La Ciotat, Banc de Banquiere in France by Genta-Jouve et al (Figure 20) [45]. No biological assessment was performed at the time and subsequent to its isolation, no further research has been reported on this interesting compound, presenting it as an attractive option for further investigation.…”
Section: Resultsmentioning
confidence: 99%
“…Structure of citharoxazole, a lead-like compound isolated from the deep-sea Mediterranean sponge, Latrunculia (Biannulata) citharistae [45]. …”
Section: Figurementioning
confidence: 99%
“…192 and Monanchora unguifera, 193 and the synthesis of mirabilin B, along with the a biosynthetic proposal, has been recently reported from Snider's group. 195 Bioassay-and LC-MS-guided fractionation of a new species of deep-sea sponge belonging to the genus Latrunculia, collected by dredging at a depth of 230 m off the Aleutian Islands, Alaska, led to the isolation of two new brominated pyrroloiminoquinones, dihydrodiscorhabdin B (175) as a dark green solid and discorhabdin Y (176) as a purple solid, along with six known pyrroloiminoquinone alkaloids, discorhabdins A, C, E, and L, dihydrodiscorhabdin C, and a benzene derivative. 195 Bioassay-and LC-MS-guided fractionation of a new species of deep-sea sponge belonging to the genus Latrunculia, collected by dredging at a depth of 230 m off the Aleutian Islands, Alaska, led to the isolation of two new brominated pyrroloiminoquinones, dihydrodiscorhabdin B (175) as a dark green solid and discorhabdin Y (176) as a purple solid, along with six known pyrroloiminoquinone alkaloids, discorhabdins A, C, E, and L, dihydrodiscorhabdin C, and a benzene derivative.…”
Section: Order Poeciloscleridamentioning
confidence: 99%